2009
DOI: 10.1523/jneurosci.0574-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Changes in Synaptic Inputs to Motoneurons in Adult Sacral Spinal Cord of a Mouse Model of Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is characterized by progressive degeneration of motoneurons. One potential mechanism is excitotoxicity. We studied the behaviors of spinal neurons using an in vitro preparation of the sacral cord from the G93A SOD1 mouse model of ALS. Measurements were conducted at presymptomatic [approximately postnatal day 50 (ϳP50)], early (ϳP90), and late (ϾP120) stages of the disease. Short-latency reflexes (SRs) in ventral roots, presumably monosynaptic, were evoked by electrical stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
73
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 51 publications
8
73
1
Order By: Relevance
“…In addition, several anatomical studies have noted an increase in the ratio of excitatory to inhibitory synapses onto MNs in the context of overall synapse loss over the course of disease (32)(33)(34). Additionally, some studies have suggested broad changes in synaptic and network function that lead to abnormal MN output in the form of irregular bursting patterns (35); however, the specific nature and ultimate consequence of such network abnormalities is not understood.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several anatomical studies have noted an increase in the ratio of excitatory to inhibitory synapses onto MNs in the context of overall synapse loss over the course of disease (32)(33)(34). Additionally, some studies have suggested broad changes in synaptic and network function that lead to abnormal MN output in the form of irregular bursting patterns (35); however, the specific nature and ultimate consequence of such network abnormalities is not understood.…”
Section: Discussionmentioning
confidence: 99%
“…This strain overexpresses the human mutant cytosolic Cu/Zn SOD1 possessing a glycine to alanine substitution at the 93rd position (G93A) [85]. These mice, expressing ∼20 copies of the transgene, develop an ALS-like disease with initial symptoms that include fine tremor or shaking and weakness in the hind limbs at 90 days postnatal (P90), leading to severe hindlimb paralysis at ∼120 days of age [85][86][87][88][89][90][91][92][93][94].…”
Section: Severe Nerve Lesionsmentioning
confidence: 99%
“…8 TRPV4 is a transmembrane Ca 2ϩ -permeable, nonselective cation channel and responsive to mechanical force, osmotic concentration, and increased temperature. 9 The potential for calcium neurotoxicity is emphasized by earlier reviews in neurodegeneration 10 with suggested roles in AD, 11 motor neuron disease, 12 and PTEN-induced putative kinase (PINK1)-associated PD. 13 Additionally, L-type calcium channel blockers have recently been shown as neuroprotective in development of idiopathic PD.…”
mentioning
confidence: 99%